Penerapan Logika Fuzzy Metode Sugeno untuk Menentukan Jumlah Produksi Keripik Kentang Usaha Rumahan Berdasarkan Data Persediaan dan Jumlah Permintaan - Esty Octa Marlina Sirait; Osi Magdalena Sitohang; Nurleily Diyanti (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2020)
The maximum profit is obtained from maximum sales. If the number of products produced by this home-based chip business is less than the amount of demand, this home-based business will lose the opportunity to get the maximum profit and vice versa. Therefore, planning the number of products in this home chip business is very important. In order to meet market demand precisely and with the appropriate amount. Factors that need to be considered in determining the number of products, among others: the amount of inventory and the amount of demand. The writing and discussion in this study is about the Application of Fuzzy Logic Sugeno Method to Determine the Amount of Purchase of home chips. To create a program design that can be expected to be applied and used, so that it helps the process of determining the amount of production based on inventory data and the amount of demand on a home-based chip business. Fuzzy Logic Sugeno method in determining the amount of chips production based on inventory data and the number of requests that have been built can be used to assist business voters in making a decision with a truth value reaching 94.887%.